Composing Poetry from Rhythm: The Influence of Song Media on the Writing Skills of Grade X Students - Nabila Nur Rizqiyah (Indonesian Journal of Education Research (IJoER), 2025)
Purpose of the study: This study aims to determine the ability to write poetry with the theme of mother by utilizing songs. Methodology: The research methodology used is a qualitative descriptive method. Data collection techniques in this study consist of several things, including observation, tests, interviews, and documentation. There are three components used in the analysis, namely, the suitability of the contents of the poem to the theme, the accuracy of word choice (diction), and the use of language style (figure of speech). Main Findings: The results of the study showed that the ability to write poetry of class X students by utilizing song media was classified as good, with an average overall score reaching 81.83%, which was included in the Good category. A total of 13 students (65%) were qualified as good, 6 students (30%) were qualified as sufficient, and 1 student (5%) was in the qualification that must be maximized, while no students achieved the qualification of very good. The use of songs as a learning medium has proven effective in improving the ability to write poetry, especially in terms of theme and language style, although in terms of diction there are still quite striking variations between participants. Novelty/Originality of this study: This study offers novelty by combining visual and auditory approaches in learning to write poetry. Students will use songs as a stimulus to enrich diction and emotional expression, so that learning becomes more systematic, creative, and effective.